Cadmium uptake kinetics in parts of the seagrass Cymodocea nodosa at high exposure concentrations - Paraskevi Malea; Theodoros Kevrekidis; Konstantina-Roxani Chatzipanagiotou; Athanasios Mogias (Journal of Biological Research - Thessaloniki, 2018)
Abstract Background Seagrass species have been recommended as biomonitors of environmental condition and as tools for phytoremediation, due to their ability to concentrate anthropogenic chemicals. This study aims to provide novel information on metal accumulation in seagrasses under laboratory conditions to support their use as a tool in the evaluation and abatement of contamination in the field. We investigated the kinetics of cadmium uptake into adult leaf blades, leaf sheaths, rhizomes and roots of Cymodocea nodosa in exposure concentrations within the range of cadmium levels in industrial wastewater (0.5–40 mg L−1). Results A Michaelis–Menten-type equation satisfactorily described cadmium accumulation kinetics in seagrass parts, particularly at 0.5–5 or 10 mg L−1. However, an S equation best described the uptake kinetics in rhizomes at 5 mg L−1 and roots at 10 and 20 mg L−1. Equilibrium concentration and uptake rate tended to increase with the exposure concentration, indicating that seagrass displays a remarkable accumulation capacity of cadmium and reflect high cadmium levels in the surrounding medium. Concerning leaf blades and rhizomes, the bioconcentration factor at equilibrium (range 73.3–404.3 and 14.3–86.3, respectively) was generally lower at higher exposure concentrations, indicating a gradual reduction of available binding sites. Leaf blades and roots accumulated more cadmium with higher rate than sheaths and rhizomes. Uptake kinetics in leaf blades displayed a better fit to the Michaelis–Menten-type equation than those in the remaining plant parts, particularly at 0.5–10 mg L−1. A marked variation in tissue concentrations mainly after the steady state was observed at 20 and 40 mg L−1, indicative of the stress induced on seagrass cells. The maximum concentrations observed in seagrass parts at 5 and 10 mg L−1 were comparatively higher than those previously reported for other seagrasses incubated to similar exposure concentrations. Conclusions Cymodocea nodosa displays a remarkable cadmium accumulation capacity and reflects high cadmium levels in the surrounding medium. Kinetic models satisfactorily describe cadmium uptake in seagrass parts, primarily in adult leaf blades, at high exposure concentrations, permitting to predict cadmium accumulation in field situations. Cymodocea nodosa appeared to be a valuable tool in the evaluation and abatement of cadmium contamination in coastal areas.